2018
DOI: 10.3390/ijms19092732
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome and IL-33: Novel Players in Sterile Liver Inflammation

Abstract: In sterile liver inflammation, danger signals are released in response to tissue injury to alert the immune system; e.g., by activation of the NLRP3 inflammasome. Recently, IL-33 has been identified as a novel type of danger signal or “alarmin”, which is released from damaged and necrotic cells. IL-33 is a pleiotropic cytokine that targets a broad range of immune cells and exhibits pro- and anti-inflammatory properties dependent on the disease. This review summarizes the immunomodulatory roles of the NLRP3 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 200 publications
(253 reference statements)
0
43
0
1
Order By: Relevance
“…Recent study has shown that hepatic inflammation and fibrogenesis are closely associated with hepatocellular necrosis and apoptosis (Lee & Friedman, ). Consistently, it has been well‐documented that danger signals such as high‐mobility group box‐1 and IL‐33 released from dying cells are critical activators in sterile inflammation that enhances the severity of several liver diseases (Gaskell, Ge, & Nieto, ; Neumann, Schiller, & Tiegs, ). Furthermore, proinflammatory cytokines such as IL‐1β and TNF‐α are closely associated with the progression of ALI because antagonizing these cytokines ameliorates the severity of liver damages induced by CCl 4 exposure (Sato et al, ; Zhu et al, ).…”
Section: Discussionmentioning
confidence: 76%
“…Recent study has shown that hepatic inflammation and fibrogenesis are closely associated with hepatocellular necrosis and apoptosis (Lee & Friedman, ). Consistently, it has been well‐documented that danger signals such as high‐mobility group box‐1 and IL‐33 released from dying cells are critical activators in sterile inflammation that enhances the severity of several liver diseases (Gaskell, Ge, & Nieto, ; Neumann, Schiller, & Tiegs, ). Furthermore, proinflammatory cytokines such as IL‐1β and TNF‐α are closely associated with the progression of ALI because antagonizing these cytokines ameliorates the severity of liver damages induced by CCl 4 exposure (Sato et al, ; Zhu et al, ).…”
Section: Discussionmentioning
confidence: 76%
“…Broadly speaking, tissue damage occurs as a result of (1) sterile injury caused by a mechanical trauma or surgery (e.g. bone fracture, organ transplant or stroke), (2) pathogenic infection (including bacterial, viral, fungal or parasitic pathogens) or (3) exposure to environmental toxicant (such as cigarette smoke or asbestos) or unbalanced diet (e.g. alcohol‐induced steatohepatitis or nonalcoholic fatty liver disease) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the NLR family pyrin domain containing 3 (NLRP3) inflammasome pathway has been proposed to be involved in the maturation of IL-33. (50) Thus far, no evidence supports the activation of the NLRP3 inflammasome in AIH. It appears that both the NLRP3 inflammasome and the IL-33 pathway can become activated in sterile inflammation-associated liver diseases; therefore, components of this inflammatory pathway represent promising new therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship between IL‐21 and IL‐33 is also expected in the pathogenesis of AIH. Furthermore, the NLR family pyrin domain containing 3 (NLRP3) inflammasome pathway has been proposed to be involved in the maturation of IL‐33 . Thus far, no evidence supports the activation of the NLRP3 inflammasome in AIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation